INFLUENCE OFSERVICEQUALITY, PRODUCT QUALITY THROUGHCUSTOMERSATISFACTION OFCUSTOMERLOYALTY IN JAMOO RESTAURANT SURABAYA - WIJAYA, IRWAN (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The purposed of this studyis to examine the effect of service quality, product quality through customer satisfaction to customer loyalty in Jamoo restaurant in Surabaya. In this study two independent variables assessed to measure customer satisfaction and loyalty as the dependent variable. This study uses SEM analysis to analyze service quality, product quality through customer satisfaction to customer loyalty. While the sampling technique in this study using purposive sampling method, so that the sample used in this study were 150 respondents. The conclusion of this study is that ssignificant effect on service quality and customer satisfaction, while product quality have no significant effect on customer satisfaction, customer satisfaction have significant effect on customer loyalty. Service quality through customer satisfaction can affect customer loyalty. Product quality through customer satisfaction can affect customer loyalty.